WORD OF MOUTH COMMUNICATION EFFECT OF USE OF THE SERVICE REVIEW (Entrepreneur, 2012)
Abstract Analysis factors influencing word communications of moth to re-service usage enthusiasm. This research object is Fairy Shop, Research problems refers to business phenomenon Fairy Shop. For the reason this research problems is as follows : what increasing re-service usage enthusiasm passed word communications of mouth. a model has been built and five research hypothesises has been formulated. Method accidental has been selected to obtain data required at this study. This research utilizes 145 respondents and overall of respondent is customers Fairy Shop Jombang. Data analysis utilizes Structural Equation Model with computer program Amos 16. Keywords: Total Quality Management, Customer and Customer Satisfaction. Result of this research shows between it that quality of service of influential positive to communications wom. Customer satisfaction of influential positive to communications wom. Commitment influential positive to commitment wom. Strength of the relation of influential positive to communications wom. Communications wom influential postif to re- service usage enthusiasm. Keywords : quality of relationship, customer satisfaction, commitment, relationship strength, word communications of mouth and re-service usage enthusiasm. Abstrak Faktor yang mempengaruhi analisis komunikasi kata ngengat kembali layanan penggunaan antusiasme. Objek penelitian ini adalah Fairy Shop, masalah penelitian mengacu pada fenomena bisnis Fairy Shop. Oleh karenanya ini masalah penelitian adalah sebagai berikut: apa yang meningkatkan re-layanan antusiasme penggunaan berlalu komunikasi dari mulut ke mulut. model telah dibangun dan lima hypothesises penelitian telah dirumuskan. Metode disengaja telah dipilih untuk memperoleh data yang diperlukan pada penelitian ini. Penelitian ini menggunakan 145 responden dan keseluruhan responden adalah pelanggan Fairy Shop Jombang. Analisis data menggunakan Structural Equation Model dengan program komputer Amos 16. Kata kunci: Total Quality Management, Pelanggan dan Kepuasan Pelanggan. Hasil penelitian ini menunjukkan bahwa antara kualitas pelayanan berpengaruh positif terhadap komunikasi WOM. Kepuasan pelanggan berpengaruh positif terhadap komunikasi WOM. Komitmen berpengaruh positif terhadap komitmen WOM. Kekuatan hubungan berpengaruh positif terhadap komunikasi WOM. Komunikasi WOM postif berpengaruh untuk kembali layanan penggunaan antusiasme. Kata kunci: kualitas hubungan, kepuasan pelanggan, komitmen, kekuatan hubungan, komunikasi dari mulut ke mulut dan re-layanan penggunaan antusiasme.